Large-scale single-cell encapsulation in microgels through metastable droplet-templating combined with microfluidic-integration. (1st July 2022) - Zhang, Haoyue; Zhang, Liyuan; An, Chuanfeng; Zhang, Yang; Shao, Fei; Gao, Yijie; Zhang, Yonghao; Li, Hanting; Zhang, Yujie; Ren, Changle; Sun, Kai; He, Wei; et al.
Abstract: Current techniques for the generation of cell-laden microgels are limited by numerous challenges, including poorly uncontrolled batch-to-batch variations, processes that are both labor- and time-consuming, the high expense of devices and reagents, and low production rates; this hampers the translation of laboratory findings to clinical applications. To address these challenges, we develop a droplet-based microfluidic strategy based on metastable droplet-templating and microchannel integration for the substantial large-scale production of single cell-laden alginate microgels. Specifically, we present a continuous processing method for microgel generation by introducing amphiphilic perfluoronated alcohols to obtain metastable emulsion droplets as sacrificial templates. In addition, to adapt to the metastable emulsion system, integrated microfluidic chips containing 80 drop-maker units are designed and optimized based on the computational fluid dynamics simulation. This strategy allows single cell encapsulation in microgels at a maximum production rate of 10 ml h −1 of cell suspension while retaining cell viability and functionality. These results represent a significant advance toward using cell-laden microgels for clinical-relevant applications, including cell therapy, tissue regeneration and 3D bioprinting.